Multiwavelength study of Fermi hard spectrum blazar B2 0806+35 using Swift, Fermi, and TACTIC observations. Issue 4 (24th September 2018) - Bhattacharyya, S; Ghosal, B; Chandra, P; Singh, K K; Yadav, K K; Tickoo, A K; Rannot, R C; Kumar, N; Marandi, P; Agarwal, N K; Kothari, M; Gour, K K; et al.
Abstract: In this work, we have reported the results of multiwavelength study of the Fermi hard spectrum blazar B2 0806+35 using data from Swift, Fermi, and TACTIC observations. We analysed Swift /UVOT, Swift /XRT, Fermi /LAT, and TACTIC data to construct the sepctral energy distribution for different epochs over last 7 yr. We modelled the spectral energy distributions using one zone leptonic blazar emission model and emission from optically thick geometrically thin accretion disc around the black hole. It is shown that the photon spectrum in the GeV–TeV energy range is steep and the source is not a good candidate to study intergalactic magnetic field. It is also shown that the accretion disc is systematically receding from the central black hole and the accretion flow is possibly advection dominated.